Ecological Momentary Assessment of HIV vs. Reproductive Health Symptoms in Women of Differing Reproductive Stages Living with HIV - Schnall, Rebecca (Menopause, 2019)
OBJECTIVE: To what extent menopause is related to symptom burden in women living with HIV (WLWH) is unclear, as a specific reproductive health analysis has seldom been undertaken, in part due to an inadequate assessment of reproductive status. The purpose of this study was to document and compare symptom frequency and attribution over 46 days and examine differences by reproductive status with a sample of 73 women living with HIV. METHODS: We conducted an ecological momentary assessment (EMA) using text messaging to follow 75 women confirmed for menopause stage with hormone profiles for 46 days. Participants were asked to respond to the following open-ended questions via a text message 3× weekly: 1) Did you have your period today? (Yes/No) 2) What were your top 3 menstrual/menopausal symptoms today? 3) What were your top 3 HIV related symptoms today? RESULTS: 74 women (mean± SD age = 51± 8 yrs, range= 24–67 yrs) completed the study (10 pre-, 20 peri, 44 post-menopause). The majority of volunteers were Black non-Hispanic (74%), non-smokers (61%), with some high school (68%) and reporting <$20,000 annual income. After controlling for co-factors, HIV symptom profiles differed by menopause stage: post-menopause predicted more fatigue, muscle aches and pains, nausea/vomiting and diarrhea (vs peri or pre-menopause). HIV-related depression was predicted by the peri stage. For reproductive symptoms, women endorsed fatigue (58%), hot flashes (52%) depression (49%), and muscle aches and pains (44%) as most common, but of these, only muscle aches and pains demonstrated group differences in period prevalence (post = 35%; peri = 45%; pre = 80%, p= 0.03) Surprisingly, hot flash frequency was similar, but fever/chills/sweats varied across menopause stage (period prevalence: post=42%; peri=15%; pre=0%, p=0.01). Reporting “a period today” predicted the profile of reproductive symptoms, but was not related to HIV symptoms. CONCLUSIONS: Although fatigue, muscle aches/pains and depression are perceived as common attributes of both HIV infection and reproductive status in WLWH, they distinguish condition-specific symptom profiles that are dependent on menopause stage.